2015
DOI: 10.1016/j.bbmt.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications after Allogeneic Hematopoietic Stem Cell Transplantation in Children: Analysis of Prognostic Factors

Abstract: Neurologic complications are serious complications after hematopoietic stem cell transplantation (HSCT) and significantly contribute to morbidity and mortality. The purpose of this study was to investigate the clinical features and prognosis in pediatric patients who had neurologic complications after allogeneic HSCT. We retrospectively reviewed the medical records of children and adolescents (19 years old or younger) who underwent allogeneic HSCT at our institution from 2000 to 2012. A total of 383 patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
3
25
1
1
Order By: Relevance
“…Our cumulative incidence of CNSC of 12.2% at 1 year and 14.5% at 5 years is lower than the majority of prior reports. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] This finding is consistent with the overall trend of reduced morbidity and mortality associated with HCT over time. 64 Despite a relatively low overall incidence of NCs we still found that development of a CNSC portends a poor prognosis and was associated with decreased PFS and OS, and increased NRM, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our cumulative incidence of CNSC of 12.2% at 1 year and 14.5% at 5 years is lower than the majority of prior reports. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] This finding is consistent with the overall trend of reduced morbidity and mortality associated with HCT over time. 64 Despite a relatively low overall incidence of NCs we still found that development of a CNSC portends a poor prognosis and was associated with decreased PFS and OS, and increased NRM, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 76%
“…Several studies have sought to define the incidence and characteristics of NCs associated with HCT, with estimates of incidence varying considerably, from~8 to 65% depending on the study design, types of NCs included, patient population and transplantation setting. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Autopsy studies have uncovered neuropathological findings in as high as 90% of patients who have died following HCT. [49][50][51] Many of these studies have found unfavorable survival among patients who develop central nervous system (CNS) complications (CNSCs).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term medical complications include severe mucositis, hepatic toxicities, septicemia, and acute GvHD, and/or an unsuccessful engraftment (Eduardo et al, 2015; Peters et al, 2015). Long-term medical complications can include infections (Ferry et al, 2007), pulmonary disease (Srinivasan et al, 2014), chronic GvHD (Alousi, Bolaños-Meade, & Lee, 2013), endocrine disease (Ferry et al, 2007), neurological problems (Kang et al, in press), as well as second malignancies and disease recurrence (Arico et al, 2010). Despite improved survival statistics, pediatric HSCT remains a risky procedure.…”
mentioning
confidence: 99%
“…55,56 Most neurologic complications occur within 100 days of transplant and manifest as seizure and encephalopathy. Seizures are most common immediately after the stem cell infusion and may be related to dimethyl sulfoxide used for cryopreservation.…”
Section: Confusion: Indirect Relation To Cancer Treatmentmentioning
confidence: 99%